Upaya Peningkatan Hasil Belajar Siswa Terhadap Pembelajaran PPKn Melalui Ketrampilan Guru Dengan Menggunakan Metode Diskusi Kelompok - I Made Sila; I Gusti Ayu Mas Darwati; Apliana Mila (Universitas Pendidikan Ganesha, 2020)
This study was Classroom Action Research (CAR) to improve students’ achievement of SMK Dwijendra Denpasar; currently students’ achievement of Pancasila and Civics Education was relatively low. Therefore, teachers were required to design learning activities that are able to develop competences both in cognitive and psychomotor domain. Learning strategies are centered on students and create a joyful atmosphere to motivate students from the beginning to the end of teaching and learning activities to improve the quality of improving students’ achievement. The main problem to be solved was whether teacher skills using group discussion method could improve student learning achievement towards of Pancasila and Civics Education in Grade XI of SMK Dwijendra Denpasar in academic year 2019/2020. The study was is the Classroom Action Research (CAR). The research subjects were 31 students of Grade XI Ak 1 of SMK Dwijendra Denpasar. The goal to be achieved was to determine the implementation of the group discussion to improve students’ achievement of Pancasila and Civics Education. The data were collected through observation technique, student learning achievement, and questionnaires. The finding showed that research analysis was implemented in two cycles. The stages of each cycle were (1) planning, (2) action, (3) observation / observation, and (4) reflection. The data collected were the activities and post-test at the end of the cycle. There was significant improvement of activities in cycle I (one); the average score of student activities which was in accordance with the evaluation score has increased. In the cycle I the students’ average score was 69% and classical completeness was 48%. Meanwhile, the average score of cycle II was 85% and the classical score was 100%. It was due to student’s responses to the approach in implementing problem-based learning model; students were comfortable in stating problems in learning that enable them to understand the concepts being taught. Thus, the teacher’s skill on group discussion could improve students’achievement of Pancasila and Civics Education reflected by percentage of students who experience greater learning completeness to improve learning achievement.